Standards and norms in the English language - Locher, Miriam A.; Strässler, Jürg (Contributions to the sociology of language, 2008)
The theme of this collection is a discussion of the notions of 'norms' and 'standards', which are studied from various different angles, but always in relation to the English language. These terms are to be understood in a very wide sense, allowing discussions of topics such as the norms we orient to in social interaction, the benchmark employed in teaching, or the development of English dialects and varieties over time and space and their relation to the standard language. The collection is organized into three parts, each of which covers an important research field for the study of norms and standards. Part 1 is entitled "English over time and space" and is further divided into three thematic subgroups: standard and non-standard features in English varieties and dialects; research on English standardization processes; and issues of standards and norms in oral production. Part 2 deals with "English usage in non-native contexts," and Part 3 is dedicated to "Issues on politeness and impoliteness." The notions of standards and norms are equally important concepts for historical linguists, sociolinguists with a variationist background, applied linguists, pragmaticians, and discourse analysts.
Keywords: English language : Standardization; English language : Variation; English language : Dialects; English language : Study and teaching : Foreign speakers; Sociolinguistics; English/language; dialectology